Determinant Variables that Affect the Financial Performance of Islamic Banking in Indonesia - Amanatun Nisfah Nurun Nikmah; Ruslan Abdul Ghofur; Heni Noviarita (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to analyze whether there is an influence of Islamic Corporate Governance, Islamic Social Responsibility, Intellectual Capital, Sharia Bank Indonesia Certificates and Profit Sharing Levels on the Financial Performance of Islamic Commercial Banks in Indonesia for the 2016-2020 period. The type of data used is secondary data obtained from the financial reports of banks, BI and OJK through published institutional reports which were analyzed using multiple linear regression with the help of the E-Views 10 Program. The results of this study are the variables Islamic corporate governance, Islamic social responsibility, and Islamic corporate governance. intellectual capital, and Bank Indonesia Sharia Certificates partially have no effect on the Financial Performance of Islamic Commercial Banks in Indonesia in 2016-2020. while the Profit Sharing Variable has an effect on the Financial Performance of Islamic Commercial Banks in Indonesia in 2016-2020. Variables Islamic Corporate Governance, Islamic Social Responsibility, Intellectual Capital, Bank Indonesia Sharia Certificates and Profit Sharing Levels Simultaneously on the Financial Performance of Islamic Commercial Banks in Indonesia in 2016-2020. Keywords: Islamic Bank, Financial Performance, Quantitative